A novel human S10F‐Hsp20 mutation induces lethal peripartum cardiomyopathy. Issue 8 (15th May 2018) - Liu, Guan‐Sheng; Gardner, George; Adly, George; Jiang, Min; Cai, Wen‐Feng; Lam, Chi Keung; Alogaili, Fawzi; Robbins, Nathan; Rubinstein, Jack; Kranias, Evangelia G.
Abstract: Heat shock protein 20 (Hsp20) has been shown to be a critical regulator of cardiomyocyte survival upon cardiac stress. In this study, we investigated the functional significance of a novel human Hsp20 mutation (S10F) in peripartum cardiomyopathy. Previous findings showed that cardiac‐specific overexpression of this mutant were associated with reduced autophagy, left ventricular dysfunction and early death in male mice. However, this study indicates that females have normal function with no alterations in autophagy but died within a week after 1‐4 pregnancies. Further examination of mutant females revealed left ventricular chamber dilation and hypertrophic remodelling. Echocardiography demonstrated increases in left ventricular end‐systolic volume and left ventricular end‐diastolic volume, while ejection fraction and fractional shortening were depressed following pregnancy. Subsequent studies revealed that cardiomyocyte apoptosis was elevated in mutant female hearts after the third delivery, associated with decreases in the levels of Bcl‐2/Bax and Akt phosphorylation. These results indicate that the human S10F mutant is associated with dysregulation of cell survival signalling, accelerated heart failure and early death post‐partum.